A 50-m/320-Gb/s DWDM FSO Communication With Afocal Scheme - Wen-Shing Tsai; Hai-Han Lu; Chung-Yi Li; Ting-Chieh Lu; Hung-Hsien Lin; Bo-Rui Chen; Chang-Jen Wu (IEEE Photonics Journal)
This paper proposes and presents the experimental demonstration of 320-Gb/s free-space optical (FSO) communication based on dense-wavelength-division-multiplexing (DWDM) technology and afocal scheme. To the best of our knowledge, this is the first one that adopts DWDM technology and afocal scheme to successfully demonstrate 50-m/320-Gb/s FSO communication. Results show that the free-space transmission distance is greatly increased by the afocal scheme and that the free-space transmission rate is significantly enhanced by the DWDM technology. DWDM FSO communication over a 50-m free-space link with a total transmission rate of 320 Gb/s $(40\;\text{Gb/s}/\lambda \times 8\lambda=320\;\text{Gb/s})$ is achieved. With the aid of a low-noise amplifier and clock/data recovery at the receiving site, good bit-error-rate (BER) performance and clear eye diagram are obtained at a 50-m/320-Gb/s operation. Such 50-m/320-Gb/s DWDM FSO communication provides the advantages of optical wireless communications for long transmission distance and high transmission rate, which is thoroughly useful for long-haul and high-speed light-based WiFi (LiFi) applications.